Plastic pollution in the ocean - Harun, Hasnida; Mohsin, Nur Izzmirza; Tahir, Rosmawati; Zulkifli, Mohd Daniel; Kasim, Norfazira; Kabir, Mohd Hafizalrisman; A. Hamid, Hazren; M. Sunar, N.; Ali, R.; Hamidon, Nuramidah; Muhamad, Mimi Suliza (Penerbit UTHM, 2020)
Plastic pollution in the ocean was first reported by scientists in the 1970s, yet in recent years it has drawn tremendous attention from the media, the public, and an increasing number of scientists spanning diverse fields, including polymer science, environmental engineering, ecology, toxicology, marine biology, and oceanography. In the oceans, the threat to marine life comes in various forms, such as overexploitation and harvesting, dumping of waste, pollution, alien species, land reclamation, dredging and global climate change. The extremely visible nature of much of this contamination is easy to convey in shocking images of piles of trash on coastlines, marine mammals entangled in fishing nets, or seabird bellies filled with bottle caps, cigarette lighters, and colourful shards of plastic. Even without these images, anyone who has visited a beach has certainly encountered discarded cigarette butts, broken beach toys left behind, or pieces of fishing gear or buoys that have washed ashore.